Perceptual feeling and time-of-day effects on high intensity exercise performance - McCormick, M. C.; Kilgore, L.; Watson, H.; Baker, J. S. (Journal of Biology of Exercise, 2012)
The present study was designed to investigate the effect of time of day and perceptual feeling on high intensity cycle ergometry and related performance during 'normal working hours'. Eleven male participants (22.9 ± 2.6yrs; 182 ± 0.06cm; 80.43 ± 14.39kg) were tested over a 12 h period (08:00-20:00 h). Every hour, on the hour, participants performed a 10s maximal leg cycle ergometry test and completed an Exercise-Induced Feeling Inventory (EFI); every hour, on the half hour, they performed a standing broad jump (SBJ), hand grip test (HG) and vertical jump (VJ). Participants were instructed that each test required maximum effort. The main results show that there were no significant differences during the 12h experimental period in any of the performance variables (P > 0.05). However, peak power output during the high intensity cycle ergometry and distance and height achieved during the SBJ and VJ test along with positive engagement all peaked at 19:00h. The results show that high intensity cycle ergometry and related physiological measures are not affected by the time of day during 'normal working hours'. However, the data suggests that maximal performance is moderately affected by motivational levels of participants and therefore when using maximal exercise tests investigators should ensure that participants are highly motivated.